2018
DOI: 10.1371/journal.pone.0194109
|View full text |Cite
|
Sign up to set email alerts
|

Altered heat nociception in cockroach Periplaneta americana L. exposed to capsaicin

Abstract: Some natural alkaloids, e.g. capsaicin and camphor, are known to induce a desensitization state, causing insensitivity to pain or noxious temperatures in mammals by acting on TRP receptors. Our research, for the first time, demonstrated that a phenomenon of pharmacological blockade of heat sensitivity may operate in American cockroach, Periplaneta americana (L.). We studied the escape reaction time from 50°C for American cockroaches exposed to multiple doses of different drugs affecting thermo-TRP. Capsaicin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 63 publications
(96 reference statements)
2
4
0
Order By: Relevance
“…Camphor was also shown to inhibit the heat-induced activation of Painless receptor in Drosophila [24]. We previously demonstrated that repeated treatment with camphor increases the latency to escape from noxious heat in the American cockroach [7]. Results obtained in the present study correspond well with these data—Insects after camphor treatment found the optimal environment for the control insects as too cold and chose higher temperatures.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Camphor was also shown to inhibit the heat-induced activation of Painless receptor in Drosophila [24]. We previously demonstrated that repeated treatment with camphor increases the latency to escape from noxious heat in the American cockroach [7]. Results obtained in the present study correspond well with these data—Insects after camphor treatment found the optimal environment for the control insects as too cold and chose higher temperatures.…”
Section: Discussionsupporting
confidence: 89%
“…Based on the obtained results and our previous experiments [5,7], we suggest that in the American cockroach:…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…For example, Drosophila larvae and adults produce a stereotyped defensive behavior in response to noxious mechanical, chemical or thermal stimuli (Tracey et al, 2003; Xu et al, 2006; Fiala, 2008; Neely et al, 2011; Im and Galko, 2012; Honjo et al, 2016; Tokusumi et al, 2017; Hu et al, 2018). This type of behavior is also evoked in cockroaches in response to thermal noxious stimuli (Gritsai et al, 2004; Gritsai et al, 2009; Maliszewska et al, 2018). With this mind, the present paper has examined the nociceptive pathway from sensory reception to motor behavior in the cockroach Periplaneta americana using primarily electrophysiological recordings.…”
Section: Introductionmentioning
confidence: 94%